Hubungan Antara Teman Sebaya dan Kejenuhan Belajar Terhadap Perilaku Merokok pada Remaja - Barkah Septian Firmanto; Vivi Leona Amelia (Journal of Bionursing, 2020)
Background. One factor which affects the act of smoking is the level of stress. Stress which is most often experienced by students is the stress of academics. The stress is caused by the academic demands faced by the students. Adolescents' act of smoking is also affected by several other factors such as releasing fatigue, imitating the parents who are smoking, and having an interaction with peers who have the habit of smoking, so that they want to try and know the taste of cigarettes. Methods. This was a descriptive quantitative research with a cross-sectional method. All eighth-grade male students in SMP X amounted to 154 students, were taken as the research samples using the total sampling technique. Results. Based on the results of the analysis with Chi-Square test on peers and the boredom of studying, the p values were 0.000 (0.05) and 0.038 (0.05) respectively. It means there is a correlation of peers toward the act of smoking. Conclusion. There is a correlation between peers and the boredom of studying to the act of smoking on adolescents in SMP X Keywords: Peers, the boredom of studying, the act of smoking